GAMBARAN PENGETAHUAN IBU TENTANG PENTINGNYA PEMBERIAN IMUNISASI BOOSTER PADA BALITA DI KLINIK SALLY TAHUN 2019 - Merlina Sinabariba (STIKes Santa Elisabeth Medan, 2019)
Infants healthycan be influenced by the environment in which infants are raised and the immunization they get is also important to do booster immunization at the age of 24 months. When children at Baduta agethey begin the second stage of immunization which is known as advanced immunization or immunization of Deuteronomy (Booster). Booster is important for boosting the immune response to vaccines which have decreased with age. If no booster is carried out, children are at risk of being unprotected when exposed to diseases that can be prevented, such as an outbreak of diphtheria. Goals : This study aims to obtain an overview of maternal knowledge about the importance of booster immunization in infants at Sally clinic 2019.The type of research is descriptive with accidental sampling techniques and data collection methods, namely primary data. Result : The results of this study indicate that from 30 respondents, having good knowledge are 8 people (26.7%), enough knowledge are 21 people (70.0%), and those with less knowledge amounted is 1 person (3.3%).Mother's knowledge of the importance of booster immunization in toddlers at Sally clinic 2019 is largely knowledgeable. Conculsion : Good information from health workers can increase maternal knowledge about booster immunization in children. Health workers are expected to be able to inform mothers, to be advised to do Booster immunization if the child has complete immunization, to increase immunity to the child's body.